Toward a Unified Theory for Complex Systems - Cui, Weicheng; Li, Rong; Pan, Lingli (European Journal of Applied Sciences, 2024)
The system serves as a general model for addressing various encountered issues, with the complexity of systems we handle increasing steadily. From the 2021 map of complexity sciences, 67 distinct theories or sub-disciplines can be counted, leading to the difficulty in selecting an appropriate theory for a particular problem. This paper aims to establish an axiomatic framework for a unified theory for complex systems, spanning from micro to macro scales and encompassing entities from non-living to living objects. The unification was carried out from fundamental concepts, fundamental assumptions and mathematical languages. The original contributions in this unified system theory include: (1) moving away from a revolution against classical mechanics and embracing its generalization, (2) offering a dualist approach to the mind-body problem instead of the monist solution of the past, and (3) introducing an active force for living objects in living state. The efficacy of this unified theory is illustrated through multiple practical applications.